Azithromycin Partially Mitigates Dysregulated Repair of Lung Allograft Small Airway Epithelium. Issue 6 (June 2020) - Ling, Kak-Ming; Garratt, Luke W.; Banerjee, Balarka; Lavender, Melanie A.; Wrobel, Jeremy P.; Musk, Michael; Martinovich, Kelly M.; Shaw, Nicole C.; Iosifidis, Thomas; Looi, Kevin; Kicic-Starcevich, Elizabeth; Sutanto, Erika N.; et al.
Abstract : Background: Dysregulated airway epithelial repair following injury is a proposed mechanism driving posttransplant bronchiolitis obliterans (BO), and its clinical correlate bronchiolitis obliterans syndrome (BOS). This study compared gene and cellular characteristics of injury and repair in large (LAEC) and small (SAEC) airway epithelial cells of transplant patients. Methods: Subjects were recruited at the time of routine bronchoscopy posttransplantation and included patients with and without BOS. Airway epithelial cells were obtained from bronchial and bronchiolar brushing performed under radiological guidance from these patients. In addition, bronchial brushings were also obtained from healthy control subjects comprising of adolescents admitted for elective surgery for nonrespiratory-related conditions. Primary cultures were established, monolayers wounded, and repair assessed (±) azithromycin (1 µg/mL). In addition, proliferative capacity as well as markers of injury and dysregulated repair were also assessed. Results: SAEC had a significantly dysregulated repair process postinjury, despite having a higher proliferative capacity than large airway epithelial cells. Addition of azithromycin significantly induced repair in these cells; however, full restitution was not achieved. Expression of several genes associated with epithelial barrier repair (matrix metalloproteinase 7, matrix metalloproteinase 3, the integrins β6 and β8, and β-catenin) were significantly different in epithelial cells obtained from patients with BOS compared to transplant patients without BOS and controls, suggesting an intrinsic defect. Conclusions: Chronic airway injury and dysregulated repair programs are evident in airway epithelium obtained from patients with BOS, particularly with SAEC. We also show that azithromycin partially mitigates this pathology. Abstract : Supplemental Digital Content is available in the text.